2022
DOI: 10.1021/acs.biomac.2c00210
|View full text |Cite
|
Sign up to set email alerts
|

Linear Poly(ethylenimine-propylenimine) Random Copolymers for Gene Delivery: From Polymer Synthesis to Efficient Transfection with High Serum Tolerance

Abstract: Naturally occurring oligoamines, such as spermine, spermidine, and putrescine, are well-known regulators of gene expression. These oligoamines frequently have short alkyl spacers with varying lengths between the amines. Linear polyethylenimine (PEI) is a polyamine that has been widely applied as a gene vector, with various formulations currently in clinical trials. In order to emulate natural oligoamine gene regulators, linear random copolymers containing both PEI and polypropylenimine (PPI) repeat units were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…Depending on the degree of substitution, succinylation of PEI chains may optimize the polymer/DNA interaction strength to balance stability-lability, and they provide stability to the vector at the serum medium, 33 thus allowing for enhanced transfection levels. 45 This output can also be linked, at least to some extent, to lower polymer toxicity. 37 Truly, these assumptions seem not to be clear enough at this moment, and we are conducting investigations in this regard to better identify the main reason linked to the outstanding performance of the BPEI-Succ chains.…”
Section: Resultsmentioning
confidence: 99%
“…Depending on the degree of substitution, succinylation of PEI chains may optimize the polymer/DNA interaction strength to balance stability-lability, and they provide stability to the vector at the serum medium, 33 thus allowing for enhanced transfection levels. 45 This output can also be linked, at least to some extent, to lower polymer toxicity. 37 Truly, these assumptions seem not to be clear enough at this moment, and we are conducting investigations in this regard to better identify the main reason linked to the outstanding performance of the BPEI-Succ chains.…”
Section: Resultsmentioning
confidence: 99%
“…These copolymers exhibited serum tolerance and were successful in transfection of the majority of C2C12 cells in the presence of serum. In this work, higher molecular weight polymers yielded greater transfection efficiency: copolymers with a degree of polymerization of 500, with ∼40–60% PPI, were most promising, resulting in 69% transfection efficiency without substantial cytotoxicity . In another study, Guégan and co-workers found that poly­(vinylamine) (PVA), an isomer of PEI, achieved efficient transfection on a variety of cell lines, including H2K2B4, C2C12, 16HBE, and DC2.4 cells …”
Section: Introductionmentioning
confidence: 81%
“…In this work, higher molecular weight polymers yielded greater transfection efficiency: copolymers with a degree of polymerization of 500, with ∼40−60% PPI, were most promising, resulting in 69% transfection efficiency without substantial cytotoxicity. 21 In another study, Gueǵan and co-workers found that poly(vinylamine) (PVA), an isomer of PEI, achieved efficient transfection on a variety of cell lines, including H2K2B4, C2C12, 16HBE, and DC2.4 cells. 22 The potential of polymeric vectors in gene delivery is increasingly recognized, while shortcomings are continually uncovered (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“… 24 28 Different N -methylated PTMI derivatives were synthesized; 24 , 29 , 30 however, they have not been the subject of antimicrobial studies. Both PEI and PTMI may be obtained in the branched, 20 linear, 27 , 31 and dendrimeric forms. 23 Linear PEI (L-PEI) and linear PTMI (L-PTMI) are usually obtained by hydrolysis of poly(alkyl-2-oxazoline)s 32 , 33 and poly(alkyl-2-oxazine)s, 28 , 34 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Its dendrimeric form has gained popularity as a nonviral transfection vector and in drug delivery systems, , although there are very limited reports on a linear form of PTMI. Different N -methylated PTMI derivatives were synthesized; ,, however, they have not been the subject of antimicrobial studies. Both PEI and PTMI may be obtained in the branched, linear, , and dendrimeric forms . Linear PEI (L-PEI) and linear PTMI (L-PTMI) are usually obtained by hydrolysis of poly­(alkyl-2-oxazoline)­s , and poly­(alkyl-2-oxazine)­s, , respectively.…”
Section: Introductionmentioning
confidence: 99%